The Management of Teachers’ Performances Assessment at the Public Middle School in Banda Aceh - Fitri, C L; Yusrizal, Yusrizal; Usman, N (FKIP Universitas Lampung, 2019)
The Management of Teachers’ Performances Assessment at the Public Middle School in Banda Aceh. Objectives: The objective of this study was to discover the management of teachers’ performance assessment at junior high schools in Banda Aceh. Methods: The method of this study was descriptive research by applying qualitative approach. The subjects were the principals and teachers. This study used observation, interview and documentation as the technique of data collection.The data analyze was completed by doing the data reduction, data presentation and verification. Findings: The results showed that: (1) The planning of teachers’ performance assessment was organized by the teachers in the beginning of a new year which the function is as the reference for the teacher to accomplish the teaching and learning process; (2) The implementation of teachers’ performance assessment was not implemented as well as possible therefore the class management does not meet the standard of the minimum service of learning; (3) The supporting factors in evaluating teacher’s performance are: supervision activity, the teachers are engaging to the teachers training and workshop (training assessment), reward to the highest result or the score. The obstruction factors in evaluating teacher’s performance are: teachers do not produce the syllabus and lesson plan, the mindset of teachers’ performance assessment is only regarded as the need of formality, the limited time to organize of the employee performance goal. Keywords: Education management, teacher performance assessment, public middle school. DOI: http://dx.doi.org/10.23960/jpp.v9.i2.201901